2017
DOI: 10.14814/phy2.13141
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of GIRK channels weakens the pre‐ and postsynaptic inhibitory activity in dorsal raphe neurons

Abstract: The serotonergic tone of the dorsal raphe (DR) is regulated by 5‐HT 1A receptors, which negatively control serotonergic activity via the activation of G protein‐coupled inwardly rectifying K+ (GIRK) channels. In addition, DR activity is modulated by local GABAergic transmission, which is believed to play a key role in the development of mood‐related disorders. Here, we sought to characterize the role of GIRK2 subunit‐containing channels on the basal electrophysiological properties of DR neurons and to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 81 publications
(155 reference statements)
1
10
1
Order By: Relevance
“…Whereas both serotonergic and GABAergic neurons in the DRN express GABA B receptors, our analysis with intracellular drug application suggest that the activation of postsynaptic GABA B receptors plays an essential role in the inhibition of serotonergic neurons. While GABA B receptor agonist-induced activation of GIRK channels and subsequent membrane hyperpolarization are well-studied 11 , 31 , 40 , GABA B antagonist-induced depolarization was subtle in present study, suggesting that inactivation of GIRK channels had little effects on GABA B antagonist-induced activation of serotonergic firing activity. However, additional researches will be required to investigate the downstream signalings of GABA B receptors and how those signalings control serotonergic activity.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Whereas both serotonergic and GABAergic neurons in the DRN express GABA B receptors, our analysis with intracellular drug application suggest that the activation of postsynaptic GABA B receptors plays an essential role in the inhibition of serotonergic neurons. While GABA B receptor agonist-induced activation of GIRK channels and subsequent membrane hyperpolarization are well-studied 11 , 31 , 40 , GABA B antagonist-induced depolarization was subtle in present study, suggesting that inactivation of GIRK channels had little effects on GABA B antagonist-induced activation of serotonergic firing activity. However, additional researches will be required to investigate the downstream signalings of GABA B receptors and how those signalings control serotonergic activity.…”
Section: Discussioncontrasting
confidence: 55%
“…Evidence suggests that GABA B receptor-mediated activation of G protein-coupled inwardly-rectifying K + (GIRK) channels inhibits serotonergic neurons through hyperpolarization of the RMP 31 . However, there was no difference in pseudo RMP between the drug-naïve and citalopram-treated groups (Supplementary Table S2 ), indicating that chronic citalopram-induced activation of serotonergic neurons was not due to hyperpolarization of RMP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that in vivo the CORT‐treated mPFC‐projecting neurons would be less responsive to afferent synaptic input than vehicle‐treated neurons. The effect of CORT on the IR of mPFC‐projecting neurons may be the result of greater ion channel conductance (McCormick, ) and the lack of a concurrent change in RMP suggests that increased chloride conductance may be responsible (Jin et al., ; Kirby et al., ; Llamosas, Ugedo, & Torrecilla, ). GABA‐ergic neurons in the periaqueductal gray are important regulators of DR 5‐HT activity (Fu et al., ; Soiza‐Reilly & Commons, ).…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal activity is controlled by the intrinsic activity of ion channels as well as by the regulatory transmitters and hormones. For 5-HT neurons, some K + channels, including SK channels (Crespi, 2010 ; Sargin et al, 2016 ), TREK1 channels (Ye et al, 2015 ) and Kir3/GIRK channels (Llamosas et al, 2015 , 2017 ; Montalbano et al, 2015 ) have been suggested as playing important roles in controlling the intrinsic neuronal activity, and modulating these channels may alleviate emotional disorders. For example, up-regulation of SK3 channels in serotonin-producing neurons are responsible for greatly reduced activity in these neurons from a model of isolated mice; blocking these inhibitory SK3 channels restores normal activity in the serotonin-producing cells and alleviates the depressive symptoms of the isolated mice (Sargin et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%